PRES secondary to autonomic dysreflexia: A case series and review of the literature. (4th July 2021) - Hubbard, Molly E.; Phillips, Aaron A.; Charbonneau, Rebecca; Squair, Jordan W.; Parr, Ann M.; Krassioukov, Andrei
Abstract : Context: Autonomic dysreflexia (AD) is a complex syndrome seen in patients with spinal cord injuries (SCI) and can be life-threatening with a significant negative impact on the health of the individual. Posterior reversible encephalopathy syndrome (PRES) is thought to be caused, in part, by rapid elevations in blood pressure; leading to posterior cerebral circulatory edema. This can result in seizures, blindness and can progress to fatal intracranial hemorrhages. Findings: Here we present two cases of patients with SCI who developed PRES from AD. Each patient was correctly diagnosed, leading to appropriate treatment of the factors leading to their AD and subsequent resolution of their PRES symptoms. Conclusions/Clinical Relevance: In SCI patients who present with new seizures, visual deficits, or other neurologic signs, PRES should be considered as a part of the differential diagnosis as a good outcome relies on rapid recognition and treatment of AD.